PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN PT. GLOBAL SHINSEI INDONESIA - Ryan Ichwanto; Dr. Ismail Razak, M.Si. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2016)
The aim of this study was to analize the influence of product quality and service quality on customers loyalty. Secondary data was obtained from PT. Global Shinsei Indonesia, while primary data was obtained from customers of PT. Global Shinsei Indonesia, Tbk through admission filling of questionnaire by using scale of Likert. In this study, accident sampling method was used and data analysis method was simple linear regression and multiple linear regression. The results of this study indicated that product quality no significant and service quality significant influenced the customers loyalty. The conclution of this study is that service quality was dominant than the product quality in influencing customers loyalty.